Gene therapy for lysosomal storage diseases: Current clinical trial prospects - Kido, Jun; Sugawara, Keishin; Nakamura, Kimitoshi (Frontiers in Genetics, 2023)
Lysosomal storage diseases (LSDs) are a group of metabolic inborn errors caused by defective enzymes in the lysosome, resulting in the accumulation of undegraded substrates. LSDs are progressive diseases that exhibit variable rates of progression depending on the disease and the patient. The availability of effective therapies, including enzyme replacement therapy, pharmacological chaperone therapy, substrate reduction therapy, and bone marrow transplantation, has increased survival time and the quality of life in some patients with LSDs. However, these therapies are not sufficiently effective, especially for neurological LSDs, because of the effect of the blood-brain barrier on blocking drug transmission or specific limiting features of each treatment. Gene therapy is a promising tool for the treatment of neurological pathology associated with LSDs. Here, we review the present state of gene therapy for several LSDs for which clinical trials have been conducted or are planned. Several clinical trials using gene therapy for LSDs are underway as phase 1/2 studies; adverse events resulting in discontinuation of clinical trials have not been reported in most of these cases. Good therapeutic outcomes have already been achieved in animal models of LSDs using viral vectors that have been or will be administered in human clinical trials. It is expected that the results of these clinical studies will lead to the practical application of gene therapy for LSDs.